ENDOTHELIAL DYSFUNCTION AND NEUROHUMORAL REGULATION OF BLOOD PRESSURE IN PATIENTS WITH SYSTEMIC SCLEROSIS - N. P. Shilkina; I. E. Yunonin; S. A. Stolyarova; A. A. Vinogradov (Научно-практическая ревматология, 2019)
Objective: to investigate the effect of endothelial dysfunction, catecholamines, and renin on the diurnal blood pressure (BP) profile in patients with systemic sclerosis (SS).Subjects and methods. Twenty-five patients with SS underwent determination of the blood count of desquamated endotheliocytes by the method described by J. Hladovec (1978), the plasma levels of endothelin-1 (ET-1), adrenaline, norepinephrine, and renin by enzyme immunoassay. All the patients underwent 24-hour BP monitoring with calculating the time index, daily index, the magnitude and rate of a morning rise in BP, as well as its daily variability.Results and discussion. Hypertension was detected in 8 (32%) patients with SS. All the patients with SS showed signs of endothelial dysfunction, as evidenced by considerable differences in endothelial activation measures compared with the control group: the mean level of ET-1 was 5.8±2.3 and 0.48±0.21 fmol/ml (p<0.05); the number of desquamated endotheliocytes was 4.50 [3.00; 7.00] and 2.10 [1.00; 3.20] • 104/l, respectively (p<0.05). The levels of adrenaline and norepinephrine in SS were significantly higher than those in the control. There were positive correlations between endothelial dysfunction and the degree of an increase in BP. Endothelial dysfunction was found to have a negative impact on the diurnal BP profile in the presence of pathological types of night-peaker and non-dipper. Conclusion. Two mechanisms, such as endothelial dysfunction and sympathoadrenal activation, are responsible for the pathogenesis of clinical symptoms of SS, including hypertension.